Mastectomy flap necrosis after nipple‐sparing mastectomy and immediate implant‐based reconstruction: An evaluation of tumescence and sharp dissection technique on surgical outcomes. Issue 6 (29th July 2019) - Ng, Troy; Knowles, Sarah; Brackstone, Muriel; Doherty, Chris
Abstract: Nipple‐sparing mastectomy (NSM) with immediate implant‐based reconstruction has better esthetic outcomes and improved patient satisfaction, in addition to being oncologically safe. A known complication of NSM is skin flap necrosis. The use of tumescence and sharp dissection may decrease this complication compared to the standard NSM technique using electrocautery. This is a retrospective review of patients who underwent a NSM between 2014 and 2017 at a regional cancer center. Tumescence with sharp dissection was compared to electrocautery. The primary outcome was skin flap necrosis. The secondary outcomes were operative time and management of the complication. A total of 62 patients underwent a NSM with 116 breasts being operated on. Full‐thickness necrosis occurred more frequently in the standard electrocautery group (12.8%) compared to the tumescence and sharp dissection group (1.3%; P  = 0.02). Partial‐thickness necrosis also occurred more frequently in the standard group (33.3%) compared to the sharp dissection group (13.0%; P  = 0.01). The operative time was significantly shorter in the sharp dissection group with the mean (SD) time being 183.5 (48.9) minutes compared to the standard electrocautery group at 202.9 (33.8) minutes ( P  = 0.03). NSM using tumescence and sharp dissection have a lower rate of the complications of partial‐ and full‐thickness necrosis. Shorter operative time was also seen with the tumescent technique.